2020
DOI: 10.1155/2020/5960375
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Inhibited Pyroptosis and Reduced the Release of IL-1β and IL-18 in the Septic Response

Abstract: Pyroptosis, an inflammatory form of programmed cell death, is the initiating event of sepsis and results in immune imbalance by releasing IL-1β and IL-18 in the early stages. Studies show that enhancing autophagy via genetic manipulation can inhibit pyroptosis and prolong the survival of a sepsis animal model, indicating a possible therapeutic strategy against sepsis. However, almost no study so far has achieved pyroptosis inhibition via pharmacological autophagy induction in a sepsis disease model. To this en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…A recent study reported that rapamycin, an autophagy agonist, reversed GSDMD-mediated pyroptosis after LPS stimulation. The authors also found that rapamycin alone did not exert an inhibitory effect on pyroptosis and emphasized the important role of autophagy in the entire process [ 56 ].…”
Section: Autophagy Is a Negative Modulator Of Pyroptosismentioning
confidence: 99%
“…A recent study reported that rapamycin, an autophagy agonist, reversed GSDMD-mediated pyroptosis after LPS stimulation. The authors also found that rapamycin alone did not exert an inhibitory effect on pyroptosis and emphasized the important role of autophagy in the entire process [ 56 ].…”
Section: Autophagy Is a Negative Modulator Of Pyroptosismentioning
confidence: 99%
“… 65 The activation of caspase-1 not only promotes pyroptosis, but also promotes the secretion of cytokines such as IL-1β and IL-18, aggravating the inflammatory storm. 74 Our flow cytometry and Western blot analyses showed that EA significantly reduced the apoptosis and pyroptosis of T lymphocytes in endotoxemic mice. EA may prevent the apoptosis and pyroptosis of T lymphocytes and immunosuppression by inhibiting the production of early inflammatory cytokines and apoptosis/pyroptosis-related proteins and signal pathways.…”
Section: Discussionmentioning
confidence: 73%
“…EV71 infection induces IL-4, IL-6, IL-12, TNF and IFN production and pyroptosis (36,41). Cells undergoing pyroptosis have been shown to produce IL-1β and IL-18 cytokines, which induce inflammation in the body (42). The present study revealed that EV71 infection induced an increase in the protein level of NLRP3, while it decreased the protein expression levels of GSDMD, pro-caspase-1 and pro-IL-1β in GES-1 cells.…”
Section: Discussionmentioning
confidence: 99%